Hematuria during prolonged administration of ketamine to treat bronchospasm and respiratory failure in a toddler. - M. Zlotolow; M. Bozych; J. D. Tobias (Pediatric Anesthesia and Critical Care Journal, 2023)
Given its ability to provide both sedation and analgesia, ketamine remains a popular agent for various clinical sce- narios in infants and children including the induction of anesthesia, procedural sedation, ICU sedation, and the treatment of pain. Additionally, it has been used as a ther- apeutic agent in the treatment of status asthmaticus and status epilepticus. In general, it has a wide therapeutic in- dex with a limited adverse effect profile that most com- monly includes tachycardia, hypertension, sialorrhea, and emergence delirium. We present a 2-year-old child with a complex past medical history, including extreme prematurity and chronic lung disease including bron- chopulmonary dysplasia (BPD), who developed hematuria following the prolonged administration of ket- amine infusion in the ICU setting. The adverse effect pro- file of ketamine is reviewed, previous reports of hematu- ria following its use presented, and potential mechanisms of this adverse effect discussed.